2021
DOI: 10.3390/molecules26092778
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Analyses and Antimicrobial Activity of Nine Kinds of Unifloral Chinese Honeys Compared to Manuka Honey (12+ and 20+)

Abstract: Honey has good antimicrobial properties and can be used for medical treatment. The antimicrobial properties of unifloral honey varieties are different. In this study, we evaluated the antimicrobial and antioxidant activities of nine kinds of Chinese monofloral honeys. In addition, headspace gas chromatography-ion mobility spectrometry (HS-GC-IMS) technology was used to detect their volatile components. The relevant results are as follows: 1. The agar diffusion test showed that the diameter of inhibition zone a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 39 publications
(56 reference statements)
0
22
2
Order By: Relevance
“…Regarding the TPC and TFC, the values obtained (0.47 ± 0.03 mg GAE g −1 and 0.05 ± 0.01 mg CAE g −1 , respectively) were slightly lower than those reported by Y.-Z. Zhang et al, 43 Gośliński et al, 44 Marshall et al, 45 and Anand et al 46 However, the TAC values (2.65 ± 0.10 μM TE g −1 by FRAP; 1.40 ± 0.13 μM TE g −1 by TEAC and 4.58 ± 0.22 μM TE g −1 by DPPH) were quite similar to those reported by Sadia Afrin et al 10 and Marshall et al 45 Besides that, 100 mg mL −1 MH did not show short term toxicity in the C. elegans nematodes as demonstrated by the results of the lethality, pharyngeal pumping and egg-laying (fertility) assays. Next, we also evaluated the effects of MH against AAPH-induced oxidative stress, since multiple lines of evidence indicate that ROS overproduction and consequently, an oxidative stress escalation, not only contributes to the aging process 4,47 but is also one of the main factors involved in the initiation and progression of neurodegenerative diseases.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Regarding the TPC and TFC, the values obtained (0.47 ± 0.03 mg GAE g −1 and 0.05 ± 0.01 mg CAE g −1 , respectively) were slightly lower than those reported by Y.-Z. Zhang et al, 43 Gośliński et al, 44 Marshall et al, 45 and Anand et al 46 However, the TAC values (2.65 ± 0.10 μM TE g −1 by FRAP; 1.40 ± 0.13 μM TE g −1 by TEAC and 4.58 ± 0.22 μM TE g −1 by DPPH) were quite similar to those reported by Sadia Afrin et al 10 and Marshall et al 45 Besides that, 100 mg mL −1 MH did not show short term toxicity in the C. elegans nematodes as demonstrated by the results of the lethality, pharyngeal pumping and egg-laying (fertility) assays. Next, we also evaluated the effects of MH against AAPH-induced oxidative stress, since multiple lines of evidence indicate that ROS overproduction and consequently, an oxidative stress escalation, not only contributes to the aging process 4,47 but is also one of the main factors involved in the initiation and progression of neurodegenerative diseases.…”
Section: Discussioncontrasting
confidence: 69%
“…Regarding the TPC and TFC, the values obtained (0.47 ± 0.03 mg GAE g −1 and 0.05 ± 0.01 mg CAE g −1 , respectively) were slightly lower than those reported by Y.-Z. Zhang et al , 43 Gośliński et al , 44 Marshall et al , 45 and Anand et al 46 However, the TAC values (2.65 ± 0.10 μM TE g −1 by FRAP; 1.40 ± 0.13 μM TE g −1 by TEAC and 4.58 ± 0.22 μM TE g −1 by DPPH) were quite similar to those reported by Sadia Afrin et al 10 and Marshall et al 45…”
Section: Discussioncontrasting
confidence: 69%
“…In Polish honey, we did not detect volatiles from ketone, pyrazine, ether, and terpene groups, but were identified compounds from groups of: Monoterpenes, disulfides, and furans, which were not detected in the Chinese samples. Moreover, the other research also showed more volatiles (60) detected in unifloral Chinese kinds of honey [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Then, we took a comb honey box on the 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 14, and 16 days, and calculated the capping ratio of comb honey. We mixed the honey samples of the same ripening day in 5 bee colonies into one sample, and the botanical origin of honey was assessed by the beekeepers and then confirmed by melissopalynological analysis [17].…”
Section: Honey Samplesmentioning
confidence: 99%
“…The determination of TFC was achieved as described in Zhang et al [17] and Tang et al [26] with the following modifications: 1 mL honey solution (0.2 g/mL) was mixed with 0.3 mL NaNO 2 (15 g/100 mL). At 6 min and 12 min, 0.3 mL Al(NO 3 ) 3 (10%) and 4 mL NaOH (1 M) were added, respectively.…”
Section: Determination Of Total Phenolic Content (Tpc) Total Flavonoids Content (Tfc) and Proline Contentmentioning
confidence: 99%